WANPRESTASI PENYEWA DALAM PENGEMBALIAN BENTUK RUKO DALAM PERJANJIAN SEWA MENYEWA DI KECAMATAN PONTIANAK KOTA - NIM. A1011171226, DWINANDA (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT Implementation of the agreement between the shophouse owner on Jalan Hm Suwignyo, Pontianak City District and 2 (two) shophouse tenants, which in civil law is included in the type of rental agreement. The agreement between the shop owner and 2 (two) renters is made in writing. The agreement gives rise to rights and obligations for the parties, because the agreement has fulfilled the conditions for the validity of an agreement as regulated in Article 1320 of the Civil Code, namely the agreement of those who bind themselves, the ability to make or say an agreement, a certain thing and a lawful reasons. The type of research used is an empirical legal research method with a descriptive analysis approach, namely by describing and analyzing the situation or facts obtained from the field at the time the research was carried out. Formulation of the problem